Comparison of microesthetic patterns in normal occlusion in relation to class I malocclusion treated with extractions of four premolars - Maranhão, Olga Benário Vieira (2019)
Introduction: The aim of this research was to compare the microesthetics characteristics of the maxillary anterior tooth in individuals with Class I malocclusion treated with four premolars extractions in relation to normal occlusion as well the evaluation of symmetry between right and left sides in both groups. Methods: The sample was divided into two groups, first one with Angle Class I malocclusion treated with four premolars extraction (mean age of 15.18 and composed by 22 female and 9 male patients), and second one with Normal Occlusion (mean age of 16.93 and comprised by 15 female and 16 male individuals) composed by 31 individuals each. Objective grading system index (OGS) was evaluated in the plaster models of both groups and then digitized in 3D 3Shape R700 scanner (3Shape A/S, Copenhagen, Denmark). The width/height proportion of anterosuperior teeth, zenith location, height of connectors and gingival contour were measured with OrthoAnalyzer 3D program. Random and systematic errors were respectively evaluated with Dahlbergs formula and paired t tests. Mann-Whitney U and t tests were applied to variables without and with normal distribution respectively. Results: In most comparison there was no significant differences between groups. It was noticed in a few situations that Class I group presented significantly greater width/height proportion in 12 than Normal Occlusion; significantly smaller gingival zenith of 23, significantly greater connector in 22 to 23 and also significantly greater gingival contour in right side in comparison to Normal Occlusion group. Both sides of Class I and Normal Occlusion groups presented symmetry. Conclusion: Four premolar extractions orthodontic treatment of Class I malocclusion provides similar microesthetic patterns as individuals with normal occlusion. Both groups generally present symmetric microesthetic characteristics.